Partial Elasticity of Demand - Moore, Henry Ludwell (Quarterly Journal of Economics, 1926)
Elasticity of demand and flexibility of prices, 394. — Equations to simple demand curves, 395. — Partial flexibility of prices, and partial elasticity of demand, 396. — Equations to demand functions revealing the partial elasticities and partial flexibilities, 398. — Conclusions, 400.